2020
DOI: 10.1111/bjh.17137
|View full text |Cite
|
Sign up to set email alerts
|

Severe congenital neutropenia‐associated JAGN1 mutations unleash a calpain‐dependent cell death programme in myeloid cells

Abstract: Severe congenital neutropenia (SCN) of autosomal recessive inheritance, also known as Kostmann disease, is characterised by a lack of neutrophils and a propensity for life-threatening infections. Using whole-exome sequencing, we identified homozygous JAGN1 mutations (p.Gly14Ser and p.Glu21Asp) in three patients with Kostmann-like SCN, thus confirming the recent attribution of JAGN1 mutations to SCN. Using the human promyelocytic cell line HL-60 as a model, we found that overexpression of patient-derived JAGN1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
(106 reference statements)
1
14
0
Order By: Relevance
“…Boztug et al 26 suggested as much, using peripheral blood neutrophils as a model, though the evidence for apoptosis was sparse and the underlying mechanism was not disclosed. We recently identified two different homozygous JAGN1 mutations in three patients with Kostmann disease, thus confirming the attribution of JAGN1 mutations to SCN 57 . We examined peripheral blood neutrophils from one of our patients (who responded poorly to recombinant G‐CSF treatment) and observed ultrastructural changes suggestive of aberrant granule exocytosis, but no signs of apoptosis (Figure 3).…”
Section: Dance Macabre: the Molecular Aetiology Of Kostmann Diseasesupporting
confidence: 74%
See 4 more Smart Citations
“…Boztug et al 26 suggested as much, using peripheral blood neutrophils as a model, though the evidence for apoptosis was sparse and the underlying mechanism was not disclosed. We recently identified two different homozygous JAGN1 mutations in three patients with Kostmann disease, thus confirming the attribution of JAGN1 mutations to SCN 57 . We examined peripheral blood neutrophils from one of our patients (who responded poorly to recombinant G‐CSF treatment) and observed ultrastructural changes suggestive of aberrant granule exocytosis, but no signs of apoptosis (Figure 3).…”
Section: Dance Macabre: the Molecular Aetiology Of Kostmann Diseasesupporting
confidence: 74%
“…Finally, we conducted a yeast two-hybrid screen and found that JAGN1 interacts with Grp78, a known regulator of the UPR as well as a regulator of calcium homeostasis in the ER. 57 In conclusion, our results showed that SCN associated JAGN1 mutations unleashed a calcium-and calpaindependent cell death in a human myeloid cell model. Further investigations are required to understand the role of calpain-mediated cell death in the pathogenesis of JAGN1-associated SCN.…”
Section: Dance Mac Ab Re: the Molecul Ar Ae Ti Ology Of Kos Tmann D I...mentioning
confidence: 54%
See 3 more Smart Citations